2013
DOI: 10.1002/zoos.201300015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the status and identity of ”︁MelaniajugicostisHanley & Theobald, 1876 - an enigmatic thiarid gastropod in Thailand (Caenogastropoda, Cerithioidea)

Abstract: Given the importance in tropical diseases caused by food-borne trematodes infecting humans, it is essential to understand the taxonomy and distribution of its first intermediate hosts, which are in Southeast Asia freshwater Cerithioidean gastropods such as the widely distributed Melanoides tuberculata. Next to the occurrence of this type species in Thailand there is a second, congeneric thiarid neglected and, therefore, remained enigmatic to date. Described as "Melania" jugicostis by Hanley & Theobald (1876) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The positions of collection sites were recorded by GPS (Garmin PLUS III, Taiwan). The localities of the relevant samples were mapped on a dot-by-dot basis to a digitally reduced version of the drainage pattern map of Thailand, as developed in Dechruksa et al (2013). This map was created using a Reliefkarte on the basis of the Global 30-Arc-Second Elevation Data (GTOPO30) from the U.S. Geological Survey and a river map from the Map/server Aquarius Geomar, and then compiled using Adobe Photoshop CS3 and Adobe Illustrator.…”
Section: Sampling Sitesmentioning
confidence: 99%
“…The positions of collection sites were recorded by GPS (Garmin PLUS III, Taiwan). The localities of the relevant samples were mapped on a dot-by-dot basis to a digitally reduced version of the drainage pattern map of Thailand, as developed in Dechruksa et al (2013). This map was created using a Reliefkarte on the basis of the Global 30-Arc-Second Elevation Data (GTOPO30) from the U.S. Geological Survey and a river map from the Map/server Aquarius Geomar, and then compiled using Adobe Photoshop CS3 and Adobe Illustrator.…”
Section: Sampling Sitesmentioning
confidence: 99%
“…This is in contrast to a pronounced correlation as to reproductive biology in Thiaridae from Australia (Glaubrecht et al 2009), where all ovo-viviparous taxa that release veligers paradoxically exhibit very restricted distributional ranges in the Jardinian biogeographical region only. It is also in contrast to differences in the Thai thiarid Melanoides jugicostis (see Dechruksa et al 2013), that was found to lack viviparous populations at least in some geographical regions and during some time of the year.…”
Section: Reproductive Biology1mentioning
confidence: 79%
“…The development of an accurate and rapid method for the detection of males in aphallic thiarids, in order to evaluate the frequency of parthenogenesis in individual populations and species or higher-level taxa, respectively, remain an essential desideratum in biosystematics research on these snails. In addition, it remains to be analysed thoroughly whether and in how far there is a correlation of partially or completely parthenogenetic populations with parasite infections by digenic trematodes, for example, in the thiarids Melanoides tuberculata (see Krailas et al 2011Krailas et al , 2012Krailas et al , 2014, in M. jugicostis (see Dechruksa et al 2013) and Tarebia granifera (Veeravechsukij et al 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glaubrecht et al (2009) and Maaß and Glaubrecht (2012) surveyed the thiarid fauna of Australia. Dechruska et al (2013) evaluated the status and identity of the nominal taxon Melania jugicostis Hanley & Theobald, 1876 from the Southeast Asian mainland, and Veeravechsukij et al (2018aVeeravechsukij et al ( , 2018b investigated the phylogeography and reproductive biology of T. granifera and its trematode parasites. However, many other named taxa have been rarely studied and, thus, remain enigmatic and even pure nomenclatorial "ghosts" with highly questionable status as evolutionary relevant entities, which hampers further insights into the systematics, biogeography, and evolution of these freshwater gastropods otherwise under scrutiny, e.g., in speciation and/ or radiation studies.…”
Section: Introductionmentioning
confidence: 99%